STRATEGI PEMANFAATAN MEDIA ONLINE TRAVEL BLOGGER DALAM PROMOSI WISATA DI KOTA BATAM - Agustina, Agustina; Cindoswari, Ageng Rara (LPPM Universitas Putera Batam, 2020)
The development of tourism in the world is growing rapidly, so too in Indonesia, especially in the city of Batam, but when talking about the world of tourism that comes to mind is how to introduce our tourism to all corners of the world by using technological developments. one of them is social media by using travel blogger. Object of this research is to find out the strategy of using blogger travel media onlind in promoting natural tourism in the city of Batam by using social media. This research uses descriptive qualitative method using the Spradley analysis model, where the spradley data analysis style is departing from extensive research then focusing and going out again. This research uses 2 data. Primary and secondary data that researchers conducted were in-depth interviews, documentation, non-participant observation and articles from the internet. The results of the study showed that the strategy of utilizing online media in promoting tourism in the city of Batam by using content either via youtube, instagram or blog was supported by the intensity of media use. itself and the routine of the travel bloggers . Keyword : Travel Bloggers , Tourism, Travel Promotion.